Investigating the course of recovery in high risk suicide using power spectral density - Nik Hashim, Nik Nur Wahidah; Wilkes, Mitchell; Salomon, Ronald (2015)

(untitled)
This pilot study attempts to address the question of whether there is a statistically significant change in patients’ vocal characteristics as they progress from the initial recording session (labeled as high risk suicidal) to the second and third recording session that was collected a few days after receiving treatments. Interview speech and reading speech were collected from five male patients and eight female patients. Using the Power Spectral Density (PSD) feature, the normalized Euclidean distance from each vector to the separating hyperplane was measured in order to capture the progression or regression of patients after three treatment sessions. One-tailed paired sample ttest demonstrates statistically significant difference between the first and second session which represents improvement. In some cases, the first and third session also demonstrates statistically significant difference which shows that patients does not experiencing relapse